Influence of site dynamic characteristics on dynamic soil-structure interaction: Comparison between 3D model and 2D models. Issue 108 (May 2018) - Liang, Jianwen; Han, Bing; Fu, Jia; Liu, Run
Abstract: The influence of site dynamic characteristics on dynamic soil-structure interaction (SSI) is studied using a three-dimensional (3D) model of a single-degree-of-freedom (SDOF) oscillator on an embedded foundation in a layered elastic half-space. The foundation has hemispherical shape, and the excitation consists of incident P, SH and SV waves. A nonsingular indirect boundary element method (IBEM) is used, with Green's functions computed for distributed loads on inclined planes. Results are shown in both frequency and time domains. The results for the 3D model are compared with those for 2D models with the same cross-section. It is shown that, the site dynamic characteristics have significant influence on the system response, and that the 2D model exaggerates their effects. 2D simplification is potentially risky in the seismic analysis of SSI, with the error of resonant-frequency estimation up to 92.3% and with the underestimation of response peak value up to 73.2% for the example in this study. Highlights: The effects of site dynamic characteristics on dynamicsoil-structure interaction. Errors of 3D dynamicsoil-structure interaction evaluated by 2D models. 3D model of a SDOF oscillator on embedded hemispherical foundation. 2D model of a SDOF oscillator on embedded semi-circular foundation. Incident P, SH and SV waves.